Potential use coconut milk as alternative to alkali solution for geopolymer production - Huseien, G.; Mirza, J.; Ismail, Mohamed; Hussin, M.; Ariffin, M. (Penerbit Universiti Teknologi Malaysia, 2016)
This work aims to verify the feasibility of utilizing coconut milk as the alkali activator solution in geopolymer production and the impact on mortar properties; geopolymer mortar is still more expensive than ordinary Portland cement mortar simply because the cost of alkali solution. Coconut milk is extensively available in Malaysia and very rich in potassium and sodium. In this research, the coconut milk was used as alkali solution (100%) at first, and then replaced by NaOH, Na2SiO3 and in the last stage mixed with NaOH and Na2SiO3 at 50%. Normal solution component of Na2SiO3 and NaOH with 8 M, and used as control samples. Binder to fine aggregate (B:A) and solution to binder (S:B) ratios were fixed at 1.5 and 0.30 respectively. Multi blend binder based geopolymer mortar are used in this study. The samples were cured with different conditions, cured at room temperature and oven temperature of 60 and 90°C. Compressive strength tests were carried out to determine the properties of hardened mortar. The samples prepared with coconut milk showed low compressive strength as compared to control samples, The results demonstrated that using coconut milk as alternative to alkali solution in geopolymer industry is not a viable option.